PENGARUH MEDIA BERBASIS LECTORA INSPIRE TERHADAP PRESTASI BELAJAR PESERTA DIDIK - Fathurrahman Wiranata (DIADIK, 2022)
This study aims to describe the influence of the lectora inspire media on the learning achievement of students in mathematics learning about measuring the angle of class IV public elementary school number 2 Pagaralam. This study used a Quasi Experimental Design method with a pretest-posttest control group design. The population in this study amounted to 41 students of class IV, with a sample of class IV A which was taken using the proportion sampling technique. The instruments used in this study were tests. The data analysis used in this research is normality test, homogeneity test and hypothesis test. The results of this study can be concluded that there is a significant effect of the use of lectora inspire-based media on the achievement learning of students